A community for students. Sign up today!
Here's the question you clicked on:
 0 viewing

This Question is Closed

03453660
 2 years ago
Best ResponseYou've already chosen the best response.2this is wrong question

terenzreignz
 2 years ago
Best ResponseYou've already chosen the best response.0@03453660 is right, but let's have some fun, anyway. Suppose a = b, where ab is not equal to 0 Then a^2 = ab a^2  b^2 = ab  b^2 (a + b)(a  b) = b(a  b) a + b = b b + b = b 2b = b 2 = 1 2  1 = 1  1 1 = 0 Granted, now we have 2 + 2 = 4 2 + 2 + 0 = 4 + 0 But since 1 = 0 2 + 2 + 0 = 4 + 1 2 + 2 = 5 QED I'm going to hell for this :D

terenzreignz
 2 years ago
Best ResponseYou've already chosen the best response.0Hey, at least spot the error in the proof...

terenzreignz
 2 years ago
Best ResponseYou've already chosen the best response.0You know for a fact that 2 + 2 = 5 is false, yet I somehow "proved" it. Something must be wrong with the proof... don't give up so quickly, look more carefully :D

sunnymony
 2 years ago
Best ResponseYou've already chosen the best response.0ya i know, this is not true in the universe

terenzreignz
 2 years ago
Best ResponseYou've already chosen the best response.0What if I tell you that it is? And I just proved it. Prove me wrong ;)

mayankdevnani
 2 years ago
Best ResponseYou've already chosen the best response.0Start with: 20 = 20 Which is the same as: 1636 = 2545 Which can also be expressed as: (2+2) 2 (9 X (2+2) = 52) 9 X 5 Add 81/4 to both sides: (2+2) 2 (9 X (2+2) + 81/4 = 52) 9 X 5 + 81/4 Rearrange the terms: ({2+2}) 9/2) 2 = (59/2) 2 Ergo: 2+2  9/2 = 5 Hence: 2 + 2 = 5 where X=multiply(*)

mayankdevnani
 2 years ago
Best ResponseYou've already chosen the best response.0i think it is correct @sunnymony

mayankdevnani
 2 years ago
Best ResponseYou've already chosen the best response.0what do you mean?

terenzreignz
 2 years ago
Best ResponseYou've already chosen the best response.0@sunnymony At some point we had (a + b)(a  b) = b(a  b) a + b = b Which arose by dividing both sides by (a  b) Can you see the problem there? @mayankdevnani I don't see how you could arrive at 2 + 2 = 5 from 2 + 2  9/2 = 5

mayankdevnani
 2 years ago
Best ResponseYou've already chosen the best response.0Start with: 20 = 20 OK Which is the same as: 1636 = 2545 OK Which can also be expressed as: (2+2) 2 (9 X (2+2) = 52) 9 X 5 Must have been written: (2+2)²  9x(2+2) = 5²  9x5 Add 81/4 to both sides: (2+2) 2 (9 X (2+2) + 81/4 = 52) 9 X 5 + 81/4 Must have been written: (2+2)²  9x(2+2) + 81/4 = 5²  9x5 + 81/4 Rearrange the terms: ({2+2}) 9/2) 2 = (59/2) 2 Must have been written: ((2+2)  9/2)² = (5  9/2)² [step a] Ergo: 2+2  9/2 = 5 Must have been written: (2+2)  9/2 = 5  9/2 [step b] Hence: 2 + 2 = 5

sunnymony
 2 years ago
Best ResponseYou've already chosen the best response.0ok but one thing this is true in the universe

mayankdevnani
 2 years ago
Best ResponseYou've already chosen the best response.0no it's just a math joke but don't take it simple....
Ask your own question
Ask a QuestionFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.